La pronunciación en el ámbito cognitivo en niños de educación inicial 2 en la Unidad Educativa Fiscomisional “Dr. Gabriel García Moreno” cantón Guano - Cajamarca Guananga, Dayana Mabel (2024)
The present research entitled; Pronunciation in the cognitive field in children of initial education 2 at the Fiscomisional Educational Unit Dr. Gabriel García Moreno Cantón Guano, aims to analyze pronunciation in the cognitive field in children of initial education 2, where it focused on analyzing the importance that exists between pronunciation with the cognitive field, prior to a process of recognition of phonemes, the same ones that are necessary in children, which will allow them to achieve significant learning. In order to better understand the subject, a methodology was carried out with a quantitative approach of a bibliographic and field nature, with a type of non-experimental cross-sectional study, in which information was obtained from bibliographic sources to reach an analysis allowing to highlight that there are different activities that help to stimulate and strengthen phonemes, we worked with a total population of children from initial level 2, where an observation sheet was used, in which information was collected for the respective tabulation, analysis and interpretation, the result of which showed that during the learning session buccofacial exercises are not frequently performed, therefore it is concluded that the proposed activities, the teacher will achieve, stimulate the attention, concentration and memory of the children, achieving better learning.